Decolonizing microfinance: An Indigenous feminist approach to transform macro-debit into micro-credit - Quinless, Jacqueline Marie; Adu-Febiri, Francis (International Sociology)
Nancy Fraser$1 (Bs theoretical critique of feminism$1 (Bs unintended facilitation of neoliberal capitalism discusses the reproduction of poverty at the grassroots among Indigenous women. This article situates the discussion in gendered colonialism to show the ways that microfinance is actually a form of structured colonization and gender oppression. The authors argue that neither the emerging literature on microfinance nor Nancy Fraser$1 (Bs theory provides Indigenous women a practical way out of the existing oppressive structures of microfinance practice. Rather, they suggest that these ideas are better understood through talking circle conversations with local Indigenous women food producers in Ghana. Through conversations, the authors learned about how these women are actively decolonizing and indigenizing microfinance and what Corntassel has described as everyday acts of resurgence and renewal within native communities. The authors reason that racialized, capitalist, gender oppression can be overcome by decolonial feminism. - Reproduced.s
Keywords: Gender; Microfinance